From planetary to societal boundaries: an argument for collectively defined self-limitation. Issue 1 (1st January 2021) - Brand, Ulrich; Muraca, Barbara; Pineault, Éric; Sahakian, Marlyne; Schaffartzik, Anke; Novy, Andreas; Streissler, Christoph; Haberl, Helmut; Asara, Viviana; Dietz, Kristina; Lang, Miriam; Kothari, Ashish; et al.
Abstract: The planetary boundaries concept has profoundly changed the vocabulary and representation of global environmental issues. We bring a critical social science perspective to this framework through the notion of societal boundaries and aim to provide a more nuanced understanding of the social nature of thresholds. We start by highlighting the strengths and weaknesses of planetary boundaries from a social science perspective. We then focus on capitalist societies as a heuristic for discussing the expansionary dynamics, power relations, and lock-ins of modern societies that impel highly unsustainable societal relations with nature. While formulating societal boundaries implies a controversial process ‒ based on normative judgments, ethical concerns, and socio-political struggles ‒ it has the potential to offer guidelines for a just, social-ecological transformation. Collective autonomy and the politics of self-limitation are key elements of societal boundaries and are linked to important proposals and pluriverse experiences to integrate well-being and boundaries. The role of the state and propositions for radical alternative approaches to well-being have particular importance. We conclude with reflections on social freedom, defined as the right not to live at others' expense. Toward the aim of defining boundaries through transdisciplinary and democratic processes, we seek to open a dialogue on these issues.